(untitled) (Sociologisk Forskning, 2000)
The present crisis in sociology: A way beyond spurious pluralism? In this article the lack of integration of sociological research and theory is highlighted. This has lead the sociological discipline into a state of intellectual disarray, which is threatening its very survival. To remedy this situation an effort is made to understand the main achievements in sociology so far. Two sociological “success stories” are identified. The first is quantitative social research, based on survey data and statistical analysis using probability theory. The second, which is better described as “a ground clearing exercise” is rational action theory. Empirical regularities uncovered by quantitative sociology should be seen as objects of major theoretical interest; theory should not be a subdiscipline in its own right. The present situation gives cause for concern - sociology as a social science has little in common with postmodernist thinkers and cultural theorists.